Hubungan Antara Religiusitas Dengan KesejahteraanPada Siswa Penghafal Al-Qur'an - Ayu Rahmawati, Devita; , Usmi Karyani S.Psi, M.Si., Psi (2017)
This study is developed based on the phenomenon of students memorized of the Al-Qur'an in SMP X who are less interested with memorizing activity of the Al-Qur'an organized by their school. This activity should make the students more religious but make them feelburdened. This is because they are required to memorize at least 1 juz. The students feel less comfortable.This study is aimed to determine the level of religiosity of junior high school students memorizedof the Al-Qur'an, to know the well-being of junior high school students memorized of the Al-Qur'an, and to know the correlation between religiosity and well-being of students.The hypothesis is a positive relationship between religiosity and wellbeing of the students memorized of the Al-Qur'an. The population were 100 students memorized the Al-Qur'an on SMP X aged 12-14 years old byusing purposive random sampling.Measuring instrument areused by the religiosity scale and well-being student scale. Itanalyzed by product moment program on SPSS 21.00 for windows. The results showedcorrelation coefficient (rxy) of 0.713 and significance (p) = 0,000; (P <0.01) with a significant positive correlation between religiosity and well-being of the students memorized of the Al-Qur'an. Category religiosity of students classified as moderate by the RE of 96.56> RH 87.5 and well-being of students classified as moderate by the RE of 98.80> RH of 95. Effective contribution of variable religiosity and well-being of the students of 50.8% and there are 49.2% other factors that affect the well-being of the students. Keywords:Well-being, Hafidz Al-Qur'an, Religiosity